RETRACTED: Combined effect of Zinc lysine and biochar on growth and physiology of wheat (Triticum aestivum L.) to alleviate salinity stress - ul Aibdin, Zain; Nafees, Muhammad; Rizwan, Muhammad; Ahmad, Shoaib; Ali, Shafaqat; Obaid, Wael A.; Alsubeie, Moodi Saham; Darwish, Doaa Bahaa Eldin; Abeed, Amany H. A. (Frontiers in Plant Science, 2023)
Salinity is one of the major threats to global food security and ranks among the most severe environmental stressors that limit crop productivity. Biochar application has received much attention in agricultural practices as it enhances crop quality and production. The present study was carried out to analyze the role of lysine zinc and biochar on growth enhancement of wheat (Triticum aestivum L. cv. PU-2011) under saline stress (EC 7.17 dSm-1). Seeds were sown in pots containing saline soil with and without 2% biochar and foliar application of Zn-lysine (0 mM, 1.0 mM and 2.0 mM) was applied at different time intervals during plant growth. Combined application of biochar and Zn-lysine 2.0 mM highly improved the physiological attributes such as chlorophyll a (37%), chlorophyll b (60%), total chlorophyll (37%), carotenoids (16%), photosynthesis rate (Pn) 45%, stomatal conductance (gs) 53%, transpiration rate (Tr) 56% and water use efficiency (WUE) 55%. The levels of malondialdehyde (MDA) 38%, hydrogen peroxide (H2O2) 62% and electrolyte leakage (EL) 48% were decreased with combine application of biochar and Zn-lysine 2.0 mM as compared to other treatments. The activities of peroxidase (POD) 44%, superoxide dismutase (SOD) 70% and ascorbate peroxidase (APX) 61% as well as catalase (CAT) 67%, were regulated with combine biochar and Zn-lysine 2.0 mM treatment. Similarly, the combined application of biochar and zinc-lysine (2.0 mM) enhanced the growth and yield attributes such as shoot length (79%), root fresh weight (62%), shoot fresh weight (36%), root dry weight (86%), shoot dry weight (39%), grain weight (57%) and spike length (43%) as compared to untreated control. The concentrations of sodium (Na) decreased whereas potassium (K), iron (Fe) and zinc (Zn) concentrations were enhanced in plants with combined application of Zn-lysine and biochar. Overall, results showed that the combined application of Zn-lysine (2.0 mM), biochar significantly inhibited the negative effect of salinity and improved the growth and physiological performance of wheat plants. The combined use of Zn-lysine and biochar might be a practical solution to tackle salt stress in plants but field studies by growing various crops under varied environmental conditions are needed before any recommendation to farmers.